The Search for Balance: Understanding and Implementing Yoga, Peace, and Democratic Education - Wiggins, Joy (In Factis Pax: Journal of Peace Education and Social Justice, 2011)
Barack Obama’s presidential campaign promoted the idea of hope for change and it seemed that the nation desperately wanted that, but somehow the hope waned and the pessimism crept back. What diminishes our sense of hope and self-empowerment? Fear? Loss of control and power over our lives? Once we lose that power, we begin to live in a space of mere survival, rather than a space of possibility and creation. This survival mode depletes our energy, and hinders the ability to create new possibilities of hope, love, compassion, honesty and empathy. The daily reality becomes a sense of complacency for what is… rather than what can be.